PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH DAN TUTOR TEMAN SEBAYA TERHADAP HASIL BELAJAR FISIKA KELAS VII MTSN KOTA SOLOK - Suhanda, Suhanda; Asmendri, Asmendri; Khaira, Kuntum (Jurnal Pembelajaran MIPA, 2014)
The learning focus on the teacher that giving effectog low learning out comes is background of research. The putpose of this research to know lerning out comes of physic that applied problem based learning and friends tutor better than use conventionalÂ learning. Kind of this research of the research with desain than randomid control group post test only design. The procedure of the research has three step: preparation, application and evalution. Using instrument of this research is learning aut comes. The data analysis using MINITAB program to complete. Measure normality, homogeneity and hypothesis. The result of sudy that we can get the average rank of experiment class 75.13 eveathough class control 66.19 and varianceexperiment class 35.57 and variance class control 67.16. from this research we get the conclusion using the application problem based lerning and friends tutor better to this differenciate of learning out comes.Key words: problem based learning, friends tutor better and learning out comes